The Effectiveness Of Sodium Polyacrylate As Landscape Catalyst - Wahiduddin, N.; Mat Desa, H.; Zainal, A. I.; Hussain, A. (Journal of Engineering and Technology (JET), 2017)
Sodium Polyacrylate is a component of Super Absorber Polymer (SAP) found in disposable diapers and act as catalysts in soil which beneficial to serves as water retention for landscape. The study was to identify the growth parameters of Tecoma Stans and investigate the effectiveness of SAP as landscape catalyst. In 2012,  Malaysia  population is 28.3 Million and generated 33,000 ton/d solid waste. From the amount of waste generated, 12.14% (4006.2 ton/d) is comprised of disposable diapers dumped in landfill. By recycling these diapers will reduce the volume of waste into landfill and simultaneously reduces the impact of pollution to environment while saving economic factor.  The study involved 5 different samples with SAP mixture (NHRN 2,3,4,5,6) and control sample (NHRN 1) during 11 weeks of study. The plant growths measured in morphological parameters were number of leaves, number of flowers, and diameter of stem and height of plants. Finding shows the positive growth in all sample with  SAP compared to control sample. The increment of diameter stem for sample NHRN 1 (46.672%), NHRN 4 (138.89%), NHRN 5 (164.29%) while increment of height in NHRN 1 (39.56%), NHRN 4 (49.43%), NHRN 5 (88.86%),  increment number of flower in NHRN 1 (2100%), NHRN 4(4300%), NHRN 5 (9400%) and increment number of leaves in NHRN 1(154.17%), NHRN 4  (283.61%) and NHRN 5 (517.98%) simultaneously. Among all samples obtained, NHRN 5 demonstrates the best in all aspects of growth. In conclusion, these studies able to prove that SAP from disposable diapers can benefit planting Tecoma Stans as a landscape catalyst.